Comparison and Analysis between the NAV6 Embolic Protection Filter and SpiderFX EPD Filter in Superficial Femoral Artery Lesions - Prakash Krishnan; Arthur Tarricone; Allen Gee; Serdar Farhan; Haroon Kamran; Annapoorna Kini; Samin Sharma (Journal of Interventional Cardiology, 2021)
Objective. To compare the safety and efficacy between the SpiderFX EPD and Emboshield NAV6 filter in the collection of embolic debris created from lower limb atherectomy procedures in patients with PAD. Materials and Methods. Between January 2014 and October 2015, 507 patients with symptomatic peripheral artery disease were treated with directional atherectomy (SilverHawk), rotational atherectomy (JetStream), or laser atherectomy (Turbo Elite) based on operator discretion. Emboshield NAV6 (n = 161) and SpiderFX (n = 346) embolic protection devices were used with each of the 3 atherectomy devices. The primary study endpoint was 30-day freedom from major adverse events (MAEs). An MAE was defined as death, MI, TVR, thrombosis, dissection, distal embolization, perforation at the level of the filter, and unplanned amputation. A descriptive comparison of the MAE rates between Emboshield NAV6 and SpiderFX embolic protection devices was conducted. Results. The freedom from major adverse event (MAE) rate was 92.0% (CI: 86.7%, 95.7%) in patients who received an Emboshield NAV6 filter compared to 91.6% (CI: 88.2%, 94.3%) in patients who received the SpiderFX filter (p=0.434). The lower limit of 86.7% freedom from major adverse event rate in the Emboshield NAV6 group was above the performance goal of 83% (p<0.0008). Conclusions. There were no significant clinical outcome differences between Emboshield NAV6 and SpiderFX EPD filters in the treatment of lower extremities. This evaluation indicates the safety and efficacy to use either filter device to treat PAD patients with lower extremity lesions.